2012
DOI: 10.1210/jc.2012-1903
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 Isoform I Controls a Panel of Proinvasive Genes Driving Aggressiveness of Papillary Thyroid Carcinomas

Abstract: Overall, our experiments demonstrate the existence of a previously unknown molecular axis that controls thyroid tumor invasiveness by altering the ability of tumor cells to interact with the surrounding microenvironment. These factors could prove to be valuable markers that permit early diagnosis of aggressive thyroid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 40 publications
8
50
0
Order By: Relevance
“…Next, we tested the effect of TSA on RUNX2 promoter activity. We previously have shown that isoform I is the major RUNX2 isoform expressed in thyroid cancer patients (16). RT-PCR analysis confirmed that isoform II was not detectable in either TPC1 or BCPAP untreated cells and that TSA did not affect its expression.…”
Section: Hdaci Inhibit Runx2 Expression In Thyroid Cancer Cell Linesmentioning
confidence: 74%
See 4 more Smart Citations
“…Next, we tested the effect of TSA on RUNX2 promoter activity. We previously have shown that isoform I is the major RUNX2 isoform expressed in thyroid cancer patients (16). RT-PCR analysis confirmed that isoform II was not detectable in either TPC1 or BCPAP untreated cells and that TSA did not affect its expression.…”
Section: Hdaci Inhibit Runx2 Expression In Thyroid Cancer Cell Linesmentioning
confidence: 74%
“…Indeed, evidence exists that the use of the two promoters is context dependent. In particular, our group and others have shown that RUNX2 isoform I is the major RUNX2 isoform in tumor cells, while isoform II seems to be restricted to skeletal cells (16,26). Noticeably, the majority of molecular signals known to control RUNX2 act through the P1 promoter, while the regulation of the P2 promoter remains largely unknown (28)(29)(30).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations